Korelasi Keterampilan Membaca Pemahaman dan Keterampilan Menulis Teks Prosedur Siswa Kelas VII SMP Negeri 1 Banuhampu Kabupaten Agam - Indriani, Rifa; Hafrison, Mohamad (Lembaga Yasin AlSys, 2024)
The aim of this research is to describe the following things. First, describe reading comprehension skills for procedural texts. Second, describe the skills of writing procedural texts. Third, explain the correlation between reading comprehension skills and procedural text writing skills. This type of research is quantitative with descriptive methods. The design used in this research is a correlation design. The population of this study was class VII students of SMP Negeri 1 Banuhampu, Agam Regency who were registered in the 2023/2024 academic year, namely 279 students. The sample in this study was determined by simple random sampling, namely 75 students. There are three results of this research. First, the procedure text writing skills of class VII students at SMP Negeri 1 Banuhampu are in the Almost Adequate (HC) qualification with an average score of 53.09. Second, the procedural text writing skills of class VII students at SMP Negeri 1 Banuhampu are in the More than Adequate (LdC) qualification with an average score of 67.63. Third, the correlation test results show (rh= 0.251) > (rt= 0.227).